Self-Assessment Kompetensi Praktik Klinis Awal Mahasiswa Keperawatan di Rumah Sakit - Hutapea, Lyna M. N. (LPPM Institut Pendidikan Nusantara Global, 2024)
Self-assessment is one way of self-assessment, which is needed to achieve the initial basic clinical practice skills for female nursing students in hospitals. Early basic clinical practice in hospitals is a learning tool for nursing students to apply nursing theory and, integrate theoretical knowledge and practical skills, which have received guidance from academic supervisors (lecturers) and clinical supervisors (hospitals). This study aims to conduct a self-assessment of the ability of female nursing students at the initial basic level of clinical practice in hospitals is the main goal of nursing education. The method used is quantitative research using descriptive-analytic research design, to answer the identification of the research problem of self-assessment of how skillful the implementation of basic clinical practice of early female nursing students in hospitals. The results showed five categories of skills: Very skilled, 12 female students (33.33%), skilled, 12 female students (33.33%), quite skilled 7 female students (18.42%), less skilled, 3 female students (7.89%), and unskilled, 2 female students (5.26%). The conclusion shows that the average percentage of Self-Assessment in performing basic initial clinical practice skills at the hospital is in the category of highly skilled, skilled, and moderately skilled. However, there are still nursing students in the less skilled and unskilled categories in relatively smaller numbers compared to those in the highly skilled, skilled,, and moderately skilled categories.